Differences in the Flavor Pleurotus eryngii at Different Growth Stages under Two Crop Rotation Systems - SONG Ling, LU Juan, LIU Yurong, LUO Ruiping, ZHOU Xing, GUI Mingying (Shipin Kexue)
Crop rotation is an efficient ecological planting system. However, the effects of different crop rotation patterns on the flavor quality of Pleurotus eryngii at various growth stages remain unclear. This study explored the differences in volatile compounds and the dynamic changes in the aroma of P. eryngii during the primary growth stage, secondary growth stage, and maturation stage under two crop rotation systems: rice followed by oyster mushroom and corn followed by oyster mushroom. Volatile compounds were identified and quantified by headspace solid phase micro-extraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS). Orthogonal partial least squares discriminant analysis (OPLS-DA) and odor activity value (OAV) were applied to analyze the differences in aroma profile and identify key aroma compounds. The results showed that 1-octen-3-ol, 3-octanone, n-heptane, methanethiol, and 3-octanol were the major aroma components of P. eryngii. The differences in the contents of volatile compounds primarily accounted for the distinct volatile characteristics observed at different growth stages. Specifically, the contents of 3-methyl-2-buten-1-ol, 3-benzyl alcohol, and 1-hexadecene overall increased during the growth of P. eryngii under rice rotation, showing an increasing and then decreasing trend. In contrast, the contents of 1-octene, styrene, and 2-phenyl-1-propene significantly increased during the growth of P. eryngii under corn rotation. Furthermore, crop rotation systems significantly impacted the aroma of P. eryngii, with the total volatile compound concentration in P. eryngii grown under rice rotation being higher when compared with the one grown under corn rotation. Based on the OAV of volatile compounds at different growth stages for both crop rotation systems, 13 key aroma compounds were identified in the rice rotation system and 10 key aroma compounds in the corn rotation system. These identified volatile compounds could serve as potential biomarkers for distinguishing P. eryngii at various growth stages.